Interventions for tobacco use cessation in people living with HIV - Mdege, ND; Shah, S; Dogar, O; Pool, ERM; Weatherburn, P; Siddiqi, K; Zyambo, C; Livingstone-Banks, J (Cochrane Collaboration, 2024)
Background The prevalence of tobacco use among people living with HIV (PLWH) is up to four times higher than in the general population. Unfortunately, tobacco use increases the risk of progression to AIDS and death. Individual‐ and group‐level interventions, and system‐change interventions that are effective in helping PLWH stop using tobacco can markedly improve the health and quality of life of this population. However, clear evidence to guide policy and practice is lacking, which hinders the integration of tobacco use cessation interventions into routine HIV care. This is an update of a review that was published in 2016. We include 11 new studies.